Limite théologique et finitude phénoménologique chez Thomas d'Aquin - Falque, Emmanuel (Revue des sciences philosophiques et théologiques, 2008)
Fidelity to Thomas Aquinas means being faithful not simply to the letter, but to the spirit of his theology. If we re-read the first questions in the Summa Theologica in the light of the modern concept of « finitude », they take on a new and different meaning. The idea of « limit » in theology is similar to that of « finitude » in phenomenology to the extent that, for Aquinas, we are human beings, and are called to remain so from start to finish. A mere observation in phenomenology, finitude becomes a summons and a call in theology. In an original and highly contemporary way, we therefore learn from Thomas Aquinas to respect and love the « limit » with which we are created - the one response, if there is one, to the question of the contemporary significance of Thomas’ thought for us today.